2001
DOI: 10.1007/s002130100746
|View full text |Cite
|
Sign up to set email alerts
|

Association between depressive behavior and absence of serotonin-dopamine interaction in the nucleus accumbens

Abstract: The inability of serotonin to stimulate dopamine release in the nucleus accumbens, thereby leading to anhedonia and lack of motivation, may therefore be an essential factor in the onset of depression and a target for modulation by antidepressant drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(101 citation statements)
references
References 17 publications
7
92
2
Order By: Relevance
“…Fluoxetine administration directly enhances 5-HT activity, which has been shown to facilitate dopamine release in the nucleus accumbens (Benloucif and Galloway 1991;De Deuwaerdere et al 1996), and increase sensitivity to reward (Sasaki-Adams and Kelley 2001). Conversely, decreased 5-HT release inhibits DA activity (Ichikawa et al 1995), a mechanism that has been linked with acquisition of anhedonia (Harrison et al 2001;Zagen et al 2001). Plausibly, therefore, reduction in positive affect during nicotine deprivation may be engendered by decreased 5-HT activity with consequent inhibition of DA release.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoxetine administration directly enhances 5-HT activity, which has been shown to facilitate dopamine release in the nucleus accumbens (Benloucif and Galloway 1991;De Deuwaerdere et al 1996), and increase sensitivity to reward (Sasaki-Adams and Kelley 2001). Conversely, decreased 5-HT release inhibits DA activity (Ichikawa et al 1995), a mechanism that has been linked with acquisition of anhedonia (Harrison et al 2001;Zagen et al 2001). Plausibly, therefore, reduction in positive affect during nicotine deprivation may be engendered by decreased 5-HT activity with consequent inhibition of DA release.…”
Section: Discussionmentioning
confidence: 99%
“…Although neurobiological theories of depression have focused on 5-HT and/or NE systems per se, recent evidence suggests a contributing role for DA in symptoms and/or efficacy of therapeutics (Zangen et al, 2001). Several antidepressant drugs (e.g.…”
Section: Depression/anxietymentioning
confidence: 99%
“…These data have important implications not only for the management and prevention of drug abuse, but also for the treatment of reduced motivation and response to reward, such as the anhedonia that is characteristic of withdrawal from drugs of abuse as well as disorders such as schizophrenia and depression. In fact, studies suggest that antidepressant efficacy at treating lack of motivation and anhedonia may involve increased DA release in the NA (Zangen et al, 2001). …”
Section: Summary and Implicationsmentioning
confidence: 99%
“…FST creates a situation of despair, and allows evaluation of the ability of the animal to adopt active strategies in inescapable stressful situation; failure to do so is indicative of a depression-like state [21,25] . We employed a modified FST, when the animals underwent a single five-minute trial [26]; such a modification of the classic Porsolt test [22] was shown to be relevant for both examining depressive state, and for screening antidepressant agents. Furthermore, since the first swim trial under conditions of classic Porsolt test plays a role of depressogenic treatment [22], such a procedure might complicate the interpretation of behavioral data in the already depressed animals.…”
Section: Behavioral Testsmentioning
confidence: 99%
“…One of core symptoms of depression is the loss of the ability to experience pleasure, referred to as anhedonia [21,26,27]. In rats, anhedonia can be assessed by the loss of taste preference; while normal animals prefer sweetened water over regular water, animals with depression do not exhibit such a preference [23,24,[28][29][30].…”
Section: Behavioral Testsmentioning
confidence: 99%